(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the effectiveness of a health program to protect pre-school children from communicable infectious diseases, and from this goal several null hypotheses were derived at a significance level of (0.05). The research sample may be from (63) children and their children divided into two groups, one experimental and the other controlling . Preparing a program commensurate with pre-school children based on activities and events commensurate with this age stage. The validity and consistency of the scale were extracted. Then the program was implemented, the post-test was applied and the results were extracted showing the effectiveness of the health program and the result was in favor of the experimental group. The research came out with a set of recommendations, the most important of which is the application of the program on Elementary school students and its application in other kindergartens. Research Summary This current research is to identify the effectiveness of a health program for preschool children’s fees from transformative diseases, and from this goal several null hypotheses were derived at a significance level of (0.05). It is suitable for pre-school children based on the activities and events that are commensurate with the stage and age. The validity and reliability of the scale was extracted. Then the experimental program treated you with the primary stage in another kindergarten .